Methods of teaching general subjects - Ruzimuratova Gavhar Shomaxatovna; Xatamova Gulnora Hamidullayevna (Zien Journals, 2022)
In this article, we can see that a few years before the new 2022, ideas were put forward to radically reform the education system, to amend many laws in this regard, and to train the younger generation to become mature professionals. In addition, the subjects in secondary schools, teaching them in a variety of ways and making the lessons interesting in an unconventional way, as well as using interactive methods, make students feel a little better about reading
Keywords: presidential decrees; methodology; general education schools; general education subjects